ANALISIS TEKNIK PENGENDALIAN KOLABORASI BALAI BESAR POM DAN DINAS KESEHATAN DALAM PENERBITAN SERTIFIKAT PANGAN INDUSTRI RUMAH TANGGA DI KOTA SEMARANG - Dhwi Ba diya Maulina Ikhsani; Sutopo Patria Jati; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2019)
In 2017, (BB POM) Food and Drug Administration Office of Central Java reported Semarang City as the one of 5 cities experiencing poisoning from 253 cases at Central Java. A preliminary survei found that some household food industry products (IRTP) that have obtained certificates for home industry food management (SP-PIRT) potentially cause poisoning because they are not in accordance with the food types permitted by law. Instead, the purpose of this study traces the problem causes using interorganizational collaboration theory, through an interaction approach between BBPOM and Health Department Office of Semarang City regarding this issuance of SP-PIRT. The method used is qualitative with in-depth interview technique to 8 informants, observation and document review assistance. The result of the study shows, there are two types of constraints faced by collaborators: The first obstacle in the initial elements, namely: the lack of communication design and human resource. Meanwhile the constraints of emergent elements are in the form of not yet determined work plans and shared targets, weak mutal trust both institutions then inconsistent and obscure communication as well as collective identity. Furthermore, the constraint control strategies used by collaborators are retreating, reconfiguring restructuring and resolving. The conclusion of this analysis describes 2 constraints that do not have the control strategy, 1 constraint was controlled inappropriately (underadjusting) and the rest has been controlled appropriately. Based on the results above, collaboration in food security could be increased by considering the compatibility between constraints and the adjustment strategy.